2019
DOI: 10.9771/gesta.v7i7.28070
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradabilidade Anaeróbia De Efluente Do Processamento Da Acerola Verde

Abstract: <p>A agroindústria aceroleira gera efluentes com elevada carga orgânica, sendo, portanto, um poluidor em potencial. O objetivo deste estudo é avaliar a biodegradabilidade anaeróbia desse efluente em termos da demanda química de oxigênio e produção de metano. Os ensaios tiveram duração de 288h e foram realizados por meio de frascos-reatores, utilizando tratamentos com diferentes concentrações de DQO (4g O<sub>2</sub>.L<sup>-1</sup>, 8g O<sub>2</sub>.L<sup>-1</s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Considering the studies performed by André et al (2019), which consider the existence of a relevant inorganic fraction and recalcitrant organic fraction in the green acerola processing effluent, the verified results demonstrate that the association of this effluent with domestic sewage contributed to a high biodegradability, since, according to Bertolino, Carvalho and Aquino (2008), the domestic sewage is essentially organic. It is observed that among the treatments at 35°C, T 1M -treatment with the highest percentage of agroindustrial effluent -presented the highest percentage of transformed soluble organic matter, that is, %BD, which indicates that this was the most biodegradable treatment.…”
Section: Resultsmentioning
confidence: 68%
“…Considering the studies performed by André et al (2019), which consider the existence of a relevant inorganic fraction and recalcitrant organic fraction in the green acerola processing effluent, the verified results demonstrate that the association of this effluent with domestic sewage contributed to a high biodegradability, since, according to Bertolino, Carvalho and Aquino (2008), the domestic sewage is essentially organic. It is observed that among the treatments at 35°C, T 1M -treatment with the highest percentage of agroindustrial effluent -presented the highest percentage of transformed soluble organic matter, that is, %BD, which indicates that this was the most biodegradable treatment.…”
Section: Resultsmentioning
confidence: 68%